Elders Living with Dementia: Nuu-Chah-Nulth First Nations Family Perspectives on Elder Healthcare - Aro, Cheryl Lavern (2022)
In Canada, the literature regarding First Nations people’s experiences with dementia is sparse, as is the literature relating to the health and wellness of Indigenous dementia caregivers. Colonization has imposed physical, psychological and structural disadvantages on Indigenous communities that impact the family’s ability to provide informal dementia care. The First Nations senior population is growing rapidly and there is a pressing need to gather knowledge about the unique needs of First Nations informal dementia caregivers. This doctoral research seeks to contribute to the growing body of literature on this vitally important topic. This thesis reports the findings from my PhD research study, which was conducted in collaboration with the Nuu-Chah-Nulth Tribal Council, and with generous support from the Nuu-Chah-Nulth community. Using an Indigenous storytelling research method, the study explored the following questions: What are the experiences of Nuu-Chah-Nulth First Nations dementia caregivers? What support services do caregivers access and what services do they perceive are lacking? Nine Nuu-Chah-Nulth caregivers shared their experiences providing support and care to a family member with memory loss, and their perspectives on memory care resources. Interviews were conducted in various locations within the Nuu-Chah-Nulth territories to gather the caregiver’s knowledge. The author’s story as an informal dementia caregiver is also interwoven throughout the dissertation. The Nuu-Chah-Nulth caregivers narratives revealed diverse and complex experiences with the following central themes and sub-themes: trauma over the life-cycle (residential school, family violence, grief and loss); pressures of care-giving (managing the symptoms of dementia, health and family dynamics); and finally, participants’ perceptions of community resources. The findings from this research reveal that Nuu-Chah-Nulth dementia caregivers and the family members they supported were still healing from the various traumas that were inflicted ...